Perbedaan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun melalui Permainan Tradisional Engklek di TK Gracia Sustain - Fely Eclasya Br Tarigan; Rizki Ramadhani (Universitas Negeri Medan, 2025)
This study aims to determine differences in gross motor skills of 5-6 Year Old Children Through the Traditional Game of Engklek at Gracia Sustain Kindergarten. This study used a quantitative approach with a pre-experimental One Group Pretest-Posttest Design. The subjects in this study were children in grades B-SKY at Gracia Sustain Kindergarten, consisting of 7 boys and 8 girls. The independent variable in this study was the traditional game of engklek, while the dependent variable was the children's gross motor skills. Data collection techniques used were observation and documentation. Based on the results of the pretest and posttest, the average pretest score was 8, and the average posttest score increased to 12. The analysis showed that there were significant differences in children's gross motor development through the traditional game of engklek. Thus, it can be concluded that the traditional hopscotch game is effective in improving gross motor skills in 5–6-year-old children at Gracia Sustain Kindergarten.